Perancangan Sistem Pengelolaan Keuangan Siswa Dengan Metode Prototype - Anastasia Meyliana (Paradigma, 2021)
Each educational institution requires that student tuition payments be made every month. Payment of school fees at SMKN 1 Klaten is done by students themselves, where the recording process is done manually. In addition to manual recording, proof of payment is also stored by pasting receipts on one sheet of opaque paper, which can result in data loss. These constraints can be reduced by establishing a school fee payment system. Before the system is built, a design is needed as a benchmark for what is needed in the system. The data collection technique used in this study was to conduct interviews with mini bank staff and observations in the Bank Mini environment. The system analysis method used is the PIECES method. Meanwhile, to make a prototype using the prototype method, namely by analyzing requirements, designing databases, designing prototypes and system testing carried out by the customer. The results of the customer check are seen from the functionality of the system, namely that the system can make it easier to enter daily transaction data which is automatically stored into a database which is then compiled into a monthly report.